Iluminação natural: contribuições para o processo de projeto em edificações escolares - Mapelli, Yulli Ribeiro (2021)
The use of natural light in indoor spaces must be done carefully, considering the quantitative and qualitative aspects of light. This assessment must be incorporated into the architectural design process in order to obtain more efficient built spaces. It is worth highlighting the relevance of considering these issues for educational environments, and light can directly affect students' development. Thus, this research aims to analyze daylight strategies in the educational architecture design process. The methodological procedures were divided into two parts: Construction of the Checklist and Construction of the script for the interview. The construction and analysis of the checklist involved the categories listed based on biliographic references, simulations with the TropLux 7 and Velux Software, analysis using the solar chart and on-site observations from an application in an existing environment. The construction of the script for the interview was based on the categories determined in the checklist and, therefore, used to analyze the insertion of daylight in the design process of school buildings by the project team of the Municipality of Vitória (PMV). As a main conclusion, it is highlighted that the studies of daylight should provide a quantitative and qualitative approach. The incorporation of daylight in the architectural design process of a school space must be understood as meeting the categories: luminous performance in the internal environment, energy efficiency of the building, integration of the internal and external environment and the dynamics of the light. The results regarding the construction and analysis of the checklist showed that the category "Luminous performance of the indoor environment", should address issues related to the integration of daylight into the indoor environment in a functional way. In the “Energy efficiency of the building” category, issues related to the integration of daylight with artificial lighting must be addressed, in order to reconcile the lighting of the luminaires. In the category “Integration of internal and external environment”, issues related to the integration of the internal environment with the external environment of the building must be addressed, observing interference from the urban environment as well as from the external view angle and the volume of the building itself. In the “Dynamics of Light” category, issues related to the design of light in internal spaces must be addressed, considering areas of full and empty, light and shadow. The analysis of the checklist applied to the existing school, compared to the interview responses, points to the need to incorporate guidelines that can assist the school building design process regarding the insertion of daylight in the four categories proposed in the research.